The Effect of Capacity Building and School Principal’s Leadership towards Teacher’s Performance - Nur Eni S; Yasir Arafat; Mulyadi Mulyadi (Universitas Bengkulu, 2020)
Capacity building is part of improving the quality of performance. This research aimed at determining the effect of capacity building and leadership of school principals on teachers’ performance in Primary School of Pulau Rimau. The population and sample in this study were teachers who taught at Primary School of Pulau Rimau, sampling was conducted using purposive sampling techniques. The results obtained there is positive and significant effect of capacity building on the performance of teachers; there is positive and significant influence of school leadership on the performance of teachers; and there is positive and significant influence of capacity building and leadership of school principals on the performance of teachers.